The neurosurgical outcome of pediatric Cushing’s disease in a single center from China: a 20-year experience - Wang, Baofeng; Zhang, Hongchi; Su, Tingwei; Ren, Jie; Sun, Qingfang; Sun, Yuhao; Bian, Liuguan (Frontiers in Endocrinology, 2025)
ObjectivePediatric Cushing’s disease (CD) is exceptionally rare and poses significant diagnostic and therapeutic challenges. This study aimed to review the diagnostic features and to evaluate the long-term surgical outcomes of transsphenoidal surgery (TSS) in Pediatric CD patients at a single tertiary center in China over two decades.MethodsA retrospective analysis included 22 pediatric CD patients (10 male, 12 female; mean age 15.8 ± 2.5 years) who underwent TSS between 2002 and 2022. Diagnosis was established through a multidisciplinary protocol involving standardized biochemical testing (LDDST, HDDST), bilateral inferior petrosal sinus sampling (BIPSS) with desmopressin stimulation (n=19), and high-resolution pituitary MRI. Microscopic TSS (MTSS) was performed before 2016 (n=11) and endoscopic TSS (ETSS) thereafter (n=11). Surgical strategy was guided by MRI and BIPSS findings. Immediate remission was defined as a postoperative serum cortisol nadir <5 μg/dL or normal 24-h urinary free cortisol (UFC). Recurrence was defined as the reappearance of hypercortisolism after remission. Mean follow-up was 29.4 months (range 2-129).ResultsMRI identified the adenoma in 18/22 patients (81.8%; 16 microadenomas, 2 macroadenomas). BIPSS indicated lateralization in 14/19 patients (73.7%), with concordance between BIPSS and MRI lateralization in 57.9% (11/19) of cases. Immediate postoperative remission was achieved in 20 patients (90.9%). The two non-remitters (one macroadenoma, one MRI- and pathology-negative) received additional therapies. Among the 20 patients with initial remission, 2 (10.0%) developed recurrence (one microadenoma, one MRI-negative) during follow-up. The sustained long-term remission rate was 81.8% (18/22).ConclusionTranssphenoidal surgery represents a highly effective first-line treatment for pediatric CD, achieving high rates of immediate (90.9%) and long-term remission (81.8%) in a specialized center. A meticulous diagnostic approach incorporating BIPSS is crucial, particularly for MRI-negative cases. While recurrence occurred in a minority of patients, primarily those with microadenomas, durable disease control is attainable for the majority with appropriate surgical management. The transition to endoscopic techniques was feasible and effective.